Ultrasound-guided microwave ablation for giant breast leiomyoma: A case report - Zhang, Siqi; Wang, Lu; Yang, Jianquan; Lu, Man (Frontiers in Oncology, 2023)
Rationale Breast leiomyoma is the rarest non-epithelial tumor of the breast. As a benign tumor, its main treatment is regular follow-up. Surgical treatment is often used in clinical practice when patients have symptoms or strongly require treatment. However, if the tumor is large or located around the nipple or areola, the cosmetic effect of surgery is not good, so it is urgent to find new treatment methods. We pioneered the use of microwave ablation in the treatment of giant breast leiomyoma and achieved good results. Patient concerns A 37-year-old female was admitted to hospital because she found a breast mass of approximately 8 cm. She had no obvious clinical symptoms, but had great psychological pressure. Diagnosis Pathological biopsy showed leiomyoma followingly the surgical operation of giant breast leiomyoma was planned. However, the breast mass was large, and the postoperative scar would affect the breast appearance. Interventions The consent was obtained from the patient and her family. The Ultrasound-guided microwave ablation was successfully performed. Outcomes The patient was followed up for 10 months, and the tumor volume ablation rate was 69.8%. The cosmetic effect of breast was excellent. Lessons To our knowledge, this is the first case to using microwave ablation (MWA) for the treatment of breast leiomyoma. Ultrasound-guided MWA can be used for the treatment of breast leiomyoma, especially when the mass is large and requires traditional surgical resection. It can effectively improve the breast aesthetics and further improve the quality of life of patients. However, it is only a case report, and needs more research to verify MWA in breast leiomyoma.